2022
DOI: 10.1128/msystems.01422-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Insights into the Kelp Microbiome from Metagenome-Assembled Genomes

Abstract: Kelp (brown algae in the order Laminariales ) are foundational species that create essential habitat in temperate and arctic coastal marine ecosystems. These photosynthetic giants host millions of microbial taxa whose functions are relatively unknown, despite their potential importance for host-microbe interactions and nutrient cycling in kelp forest ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 100 publications
4
44
0
1
Order By: Relevance
“…The abundance of dissolved organic carbon from macrophytes ( 21 23 , 48 ) might select for heterotrophic metabolisms. Indeed, we found an abundance of genes for dissolved organic matter assimilation and transport in all metagenomes, suggesting that heterotrophy may be common in macrophyte-associated microbial communities ( 43 ). Improved characterization of the components of dissolved organic matter and the genomes of hosts will allow us to better assess the complementarity in resource supply by hosts and resource use by microbes, with critical implications for the carbon cycle ( 58 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The abundance of dissolved organic carbon from macrophytes ( 21 23 , 48 ) might select for heterotrophic metabolisms. Indeed, we found an abundance of genes for dissolved organic matter assimilation and transport in all metagenomes, suggesting that heterotrophy may be common in macrophyte-associated microbial communities ( 43 ). Improved characterization of the components of dissolved organic matter and the genomes of hosts will allow us to better assess the complementarity in resource supply by hosts and resource use by microbes, with critical implications for the carbon cycle ( 58 ).…”
Section: Discussionmentioning
confidence: 95%
“…For (iv) and (v), we assembled suites of genes which we searched for within each MAG (suites are described in Data Set S1 , Sheet 3). To expand our functional analysis of the kelp microbiome, we included 32 MAGs from the surface of N. luetkeana blades ( 43 ), derived from metagenome samples TAT_2019a and TAT_2019b, collected from Tatoosh Island at the same time as the samples in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus was also found abundantly on the youngest parts of the sister species S. japonica (Balakirev et al, 2012;Zhang et al, 2020) and other kelps like L. setchellii (Lemay et al, 2021), L. hyperborea (Bengtsson et al, 2012), Macrocystis pyrifera, and Nereocystis luetkeana (Weigel and Pfister, 2019;Ramírez-Puebla et al, 2022), reinforcing the idea of a strong association between Granulosicoccus and the kelp tissue. This genus might help its host by providing vitamins (vitamin B12, for example) and reduced nitrogen (Kang et al, 2018;Capistrant-Fossa et al, 2021;Weigel et al, 2022). In the same vein, the genus Algitalea (Flavobacteriaceae; 3% of total reads) was one of the "apex" bacterial core genera.…”
Section: Discussionmentioning
confidence: 99%
“…Different conditions can enhance the ability to understand the microbiome community (Figure 2A). Metagenomic sequencing from rotten vesicles of S. fusiforme contained ~15% host DNA, which suggests that the mixture of tissue and bacterial genomes is an effective way to get bacterial sequences, which are also used in kelp-associated microbiome analysis [37]. The analysis of GC content and microbial community has shown that compared with the change in the environment, the effect of genetic information is still limited.…”
Section: Discussionmentioning
confidence: 99%